Synthesis method of ultrathin perylene diimide polymer / titanium dioxide photoanode and its application in photoelectrolysis of water to produce hydrogen

CN116657188BActive Publication Date: 2026-11-03JIANGSU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310426082.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2026-11-03
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The recombination of photogenerated charge carriers in TiO2 nanorod array photoanodes limits the efficiency of photoelectrochemical water splitting, a problem that current technologies have failed to effectively solve. This study aims to improve the performance of photoelectrochemical water splitting by constructing an inorganic-organic composite material system to reduce photogenerated charge carrier recombination.

Method used

An inorganic-organic hybrid system was formed by loading ultrathin perylene imide polymer (PDIP) onto a TiO2 nanorod array. The PDIP was then modified onto the surface of the TiO2 nanorods using electrostatic self-assembly technology to promote charge separation.

Benefits of technology

It significantly improves the photoelectrochemical water splitting performance of TiO2 photoelectrodes, more than doubling the photocurrent density and doubling the surface charge separation efficiency, thus providing the possibility for the industrial application of TiO2 photoanodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116657188B_ABST
    Figure CN116657188B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of semiconductor nano photoelectric material, and relates to a synthesis method of an ultrathin perylene imide polymer / titanium dioxide photoanode, which comprises the following steps: dispersing PDIP in deionized water, continuously ultrasonicating for 7-14 days, centrifuging, collecting supernatant, and obtaining a thin-layer PDIP solution; placing a TiO2 photoanode in the PDIP solution, standing and adsorbing for 2-12 hours, taking out and airing, and drying at 60 DEG C. The prepared photoanode is applied to photoelectric hydrolysis for hydrogen production. The application loads ultrathin perylene imide polymer (PDIP) nanosheets on titanium dioxide (TiO2) nanorod arrays, constructs an inorganic-organic hybrid system, and promotes charge separation on the surface of the photoanode. The photoelectrochemical water splitting performance of the TiO2 photoelectrode with the introduction of PDIP is significantly better than that of the original TiO2 photoelectrode, and the photoelectrochemical water splitting performance is greatly improved. The application has simple preparation process, is green, and has good repeatability, and provides a feasible scheme for the industrial application of TiO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor nano-optoelectronic materials technology, and relates to photoanodes, particularly to a method for synthesizing an ultrathin perylene imide polymer / titanium dioxide photoanode and its application in photoelectric water splitting for hydrogen production. Background Technology

[0002] Compared to current industrial hydrogen production methods, photoelectrochemical water splitting for hydrogen production aligns better with the principles of low cost, high efficiency, and sustainability. The four-electron reaction occurring at the photoanode limits the catalytic efficiency of photoelectrochemical water splitting, making the selection of a suitable photoanode material crucial. TiO2 nanorod arrays have been widely used in photoelectrochemical water splitting due to their advantages such as good stability, mature preparation methods, and easily controllable performance. The one-dimensional rod-like nanostructure of TiO2 nanorod array photoanodes facilitates directional charge transport, while the three-dimensional ordered spatial structure not only promotes multiple light reflections but also increases light absorption. However, the photoelectrochemical performance of TiO2 is significantly affected by the rapid recombination of photogenerated charge carriers on its surface. Therefore, reducing the recombination of photogenerated charge carriers is an important measure to improve the photoelectrochemical water splitting performance of TiO2 photoanodes.

[0003] In recent years, researchers have employed various methods to reduce the recombination of photogenerated carriers. A recent research hotspot is the construction of inorganic-organic hybrid systems to address this problem. On the one hand, most organic semiconductors possess excellent light absorption coefficients and can serve as photosensitizers to broaden the light absorption range of metal oxides. On the other hand, some organic materials can be combined with inorganic semiconductors to reduce charge recombination. Furthermore, by simply modifying organic compounds, their structure and electron density can be altered, leading to even better photoelectrochemical water splitting performance.

[0004] Perylene imide polymers are widely used in photocatalytic hydrogen production due to their high electron mobility and large conjugated planar structure. PDIP, as a perylene imide polymer, has a large planar conjugated structure at its central perylene core, formed by five linked benzene rings, which ensures its good stability. Introducing carbonyl functional groups from urea at the outer imide groups creates an asymmetric spatial structure within PDIP. This asymmetric spatial structure results in a strong dipole moment, allowing for the formation of an internal electric field. Summary of the Invention

[0005] The purpose of this invention is to provide a method for modifying TiO2 photoelectrodes using ultrathin PDIP.

[0006] The technical solution is as follows: First, a neatly arranged rutile TiO2 nanorod photoelectrode is grown on conductive glass (FTO) using a hydrothermal method. Then, an ultrathin perylene imide polymer (PDIP) after ultrasonic treatment is electrostatically self-assembled onto the TiO2 nanorods to promote charge separation, thereby enhancing the photoelectrochemical water splitting performance.

[0007] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: PDIP was dispersed in deionized water, sonicated continuously for 7–14 days, centrifuged, and the supernatant was collected to obtain a thin layer of PDIP solution. The TiO2 photoanode was placed in the PDIP solution and allowed to stand for 2–12 hours for adsorption reaction. After that, it was taken out and air-dried, and then dried at 60°C.

[0008] In a preferred embodiment of the present invention, during step A, ultrasonic stripping is performed continuously for 7 days.

[0009] In a preferred embodiment of the present invention, in step A, the mass / volume ratio of the added PDIP to deionized water is 10-100 mg:100 mL, preferably 10 mg:100 mL.

[0010] The PDIP of this invention is prepared by the following steps: mixing 0.78 g of 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate evenly, and heating at 140°C for 5 h; then adding 20.0 mL of 1 mol / L HCl and stirring for 15 min; centrifuging the resulting solution with water and ethanol until the supernatant becomes colorless; collecting the precipitate; and vacuum drying at 80°C overnight to obtain PDIP.

[0011] In a preferred embodiment of the present invention, in step B, the volume of the PDIP solution is 10 mL and the reaction time is 8 h.

[0012] The TiO2 photoanode of this invention is prepared by the following steps: under magnetic stirring, 0.72 mL of tetrabutyl titanate is slowly added dropwise to 10 mL of 6 mol / L hydrochloric acid aqueous solution, stirred evenly, and then poured into a reaction vessel. A piece of cleaned FTO is placed in the vessel and sealed. The vessel is heated at 180°C for 6 h, cooled to room temperature, and then the FTO is removed, rinsed with deionized water, and dried. Finally, the FTO is placed in a muffle furnace and annealed at 550°C for 2 h. The FTO coated with TiO2 nanorods is washed with deionized water and dried at 60°C to obtain TiO2.

[0013] To differentiate the performance improvement of TiO2 photoelectrode by PDIP, this invention introduces a blank control TiO2 photoelectrode (abbreviated as TiO2).

[0014] The charge transfer between PDIP and TiO2 in this invention was determined by X-ray photoelectron spectroscopy (XPS), the crystal structure of the material was determined by high-resolution transmission electron microscopy (HRTEM), and the surface morphology was identified by field emission scanning electron microscopy (FESEM).

[0015] Another objective of this invention is to apply PDIP / TiO2 as a working electrode in the field of photoelectrochemical water splitting for hydrogen production.

[0016] The photoelectrochemical water splitting performance of the prepared photoanode was tested under xenon lamp irradiation (300 W) as follows: The test was conducted under a CHI 760E electrochemical workstation. A 1 mol / L borate buffer solution was added to the electrolytic cell as the electrolyte. An Ag / AgCl electrode was used as the reference electrode, a platinum sheet was used as the counter electrode, and the prepared TiO2 electrode was used as the working electrode. Linear sweep voltammetry, transient photocurrent density, and electrochemical impedance were measured. Beneficial effects

[0017] This invention constructs an inorganic-organic hybrid system by loading ultrathin perylene imide polymer (PDIP) nanosheets onto a titanium dioxide (TiO2) nanorod array, promoting charge separation on the photoanode surface. Furthermore, the photoelectrochemical water splitting performance of the PDIP-introduced TiO2 photoelectrode is significantly superior to that of the original TiO2 photoelectrode, resulting in a substantial improvement in photoelectrochemical water splitting performance. While TiO2 is a promising semiconductor material for industrial application in photoelectrochemical water splitting, its relatively low photocurrent density limits the application of TiO2 photoanodes. This invention provides a simple, environmentally friendly, and reproducible preparation process, offering a feasible solution for the industrial application of TiO2. Attached Figure Description

[0018] Figure 1 (a) FESEM, (b) (c) HRTEM and (d) corresponding elemental mapping plots of PDIP / TiO2; Figure 2 Fourier transform infrared spectra of PDIP, TiO2, and PDIP / TiO2; Figure 3 AFM image of ultrathin PDIP nanosheets; Figure 4 (a) Photocurrent density of PDIP / TiO2 at different reaction times under 1.23 V conditions; (b) N atom content of PDIP / TiO2 photoanodes at different reaction times obtained by XPS;

[0019] Figure 5 (a) Untreated TiO2 and PDIP / TiO2 j-(b) Potential curve; (c) Instantaneous photocurrent response curve; (d) Charge separation efficiency of TiO2 and PDIP / TiO2 photoanodes; (e) ABPE curves of TiO2 and PDIP / TiO2 photoanodes. Implementation

[0020] The present invention will be described in detail below with reference to embodiments, so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0021] Unless otherwise specified, the terms used herein (including technical terms) shall be interpreted as having the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It will also be understood that the terms used herein shall be interpreted as having the same meaning as they have in the context of this specification and related art, and shall not be interpreted in an idealized or excessive manner, unless specifically defined herein. Example 1

[0022] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: A. Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring until homogeneous, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C. B. Preparation of PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 2 h, and then dried in an oven at 60 °C.

[0023] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 0.52 mA cm⁻¹. -2 It is 1.33 times that of the original TiO2. Example 2

[0024] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: A. Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring until homogeneous, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C. B. Preparation of PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 4 h, and then dried in an oven at 60 °C.

[0025] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 0.68 mA cm⁻¹. -2 It is 1.74 times that of the original TiO2. Example 3

[0026] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: A. Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring until homogeneous, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C. B. Preparation of PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 6 h, and then dried in an oven at 60 °C.

[0027] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 0.89 mA cm⁻¹. -2 It is 2.28 times that of the original TiO2. Example 4

[0028] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: A. Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring thoroughly, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C.

[0029] B. Preparation of PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 8 h, and then dried in an oven at 60 °C.

[0030] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 1.19 mA cm⁻¹. -2 It is 3.05 times that of the original TiO2.

[0031] Characterization and analysis of PDIP / TiO2 photoanode materials pass Figure 1 It can be seen that the present invention successfully prepared TiO2 with a nanorod array structure. After ultrasonic treatment, PDIP exhibits a clear thin-layer nanosheet structure, which is loaded onto the surface of TiO2, while the surface morphology of TiO2 is not damaged.

[0032] Figure 2 These are Fourier transform infrared spectra of different prepared materials. It can be seen that PDIP contains imide functional groups and no acid anhydrides, proving the successful preparation of PDIP.

[0033] Figure 3AFM image of ultrathin PDIP nanosheets. By performing AFM testing on PDIP after sonication, it can be found that ultrathin PDIP nanosheets with a thickness of only 2.2 nm were obtained through sonication.

[0034] Figure 4 This compares the photoelectrochemical water splitting performance of PDIP / TiO2 photoanodes with different reaction times and PDIP content. The photocurrent density reaches its maximum at a reaction time of 8 h. Thereafter, as the reaction time increases, the photocurrent density remains unchanged because the PDIP content in the photoanode remains constant.

[0035] Figure 5 The photoelectrochemical water splitting performance of the PDIP / TiO2 photoelectrode was tested, and the photocurrent density of PDIP / TiO2 reached 1.19 mA cm⁻¹. -2 It is about three times that of the original TiO2 photoelectrode, and the surface charge separation efficiency is twice that of the original TiO2 photoelectrode. Example 5

[0036] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring until homogeneous, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C. Preparation of B PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 10 h, and then dried in an oven at 60 °C.

[0037] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 1.19 mA cm⁻¹. -2 It is 3.05 times that of the original TiO2. Example 6

[0038] A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide (PDIP / TiO2) photoanode includes the following steps: Preparation of TiO2 photoelectrode: Under magnetic stirring, 0.72 mL of tetrabutyl titanate was slowly added dropwise to a beaker containing 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring until homogeneous, the solution was poured into a reaction vessel, and a piece of cleaned FTO was placed inside. The reaction vessel was placed in a high-temperature oven and heated at 180 °C for 6 h. After the reaction vessel cooled to room temperature, the FTO was removed, rinsed with deionized water, and dried. Finally, the reacted FTO was placed in a muffle furnace and annealed at 550 °C for 2 h. The TiO2 nanorod-coated FTO was washed with deionized water and dried in an oven at 60 °C. Preparation of B PDIP / TiO2 photoanode: (1) 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole and 0.37 g of zinc acetate were mixed and added to a 100 mL three-necked flask. The mixture was heated at 140 °C for 5 h. Then 20.0 mL of 1 mol / L HCl was added to the three-necked flask after the reaction and stirred for 15 min. The resulting solution was centrifuged with water and ethanol until the supernatant became colorless. The precipitate was collected and dried under vacuum at 80 °C overnight to obtain PDIP. (2) The prepared PDIP was ultrasonically dispersed in deionized water and ultrasonicated continuously for one week to obtain a thin layer of PDIP. The solution was centrifuged and the supernatant was collected. A piece of the prepared TiO2 photoanode was placed in 10 mL of PDIP solution and reacted for 12 h, and then dried in an oven at 60 °C.

[0039] The fabricated PDIP / TiO2 photoanode was used as the working electrode, and linear sweep voltammetry was performed. The photocurrent density of the sample was 1.19 mA cm⁻¹. -2 It is 3.05 times that of the original TiO2.

[0040] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for synthesizing an ultrathin perylene imide polymer / titanium dioxide photoanode, characterized in that, Includes the following steps: A. Disperse PDIP in deionized water, sonicate continuously for 7–14 days, centrifuge, collect the supernatant to obtain a thin-layer PDIP solution. The PDIP is prepared via the following steps: Mix 0.78 g of 3,4,9,10-perylenetetracarboxylic acid dianhydride (PTCDA), 0.12 g of urea, 5.0 g of imidazole, and 0.37 g of zinc acetate evenly, heat at 140 °C for 5 h; then add 20.0 mL of 1 mol / L HCl and stir for 15 min. Centrifuge the resulting solution with water and ethanol until the supernatant becomes colorless, collect the precipitate, and vacuum dry at 80 °C overnight to obtain the final product. B. The TiO2 photoanode is placed in PDIP solution and allowed to stand for adsorption reaction for 2-12 hours. After removal, it is air-dried and then dried at 60°C. The TiO2 photoanode is prepared by the following steps: Under magnetic stirring, 0.72 mL of tetrabutyl titanate is slowly added dropwise to 10 mL of 6 mol / L hydrochloric acid aqueous solution. After stirring evenly, the solution is poured into a reaction vessel, a piece of cleaned FTO is placed on it, and the vessel is sealed. The reaction vessel is heated at 180°C for 6 hours. After cooling to room temperature, the FTO is removed, rinsed with deionized water, and dried. Finally, the FTO is placed in a muffle furnace and annealed at 550°C for 2 hours. The FTO coated with TiO2 nanorods is washed with deionized water and dried at 60°C.

2. The method for synthesizing the ultrathin perylene imide polymer / titanium dioxide photoanode according to claim 1, characterized in that: In step A, during ultrasonic ablation, continuous ultrasound is performed for 7 days.

3. The method for synthesizing the ultrathin perylene imide polymer / titanium dioxide photoanode according to claim 1, characterized in that: In step A, the mass / volume ratio of the added PDIP to deionized water is 10-100 mg: 100 mL.

4. The method for synthesizing the ultrathin perylene imide polymer / titanium dioxide photoanode according to claim 3, characterized in that: In step A, the mass / volume ratio of the added PDIP to deionized water is 10 mg: 100 mL.

5. The method for synthesizing the ultrathin perylene imide polymer / titanium dioxide photoanode according to claim 1, characterized in that: In step B, the volume of the PDIP solution is 10 mL.

6. The method for synthesizing the ultrathin perylene imide polymer / titanium dioxide photoanode according to claim 1, characterized in that: In step B, the TiO2 photoanode is placed in the PDIP solution and allowed to stand for 8 hours for adsorption reaction.

7. The ultrathin perylene imide polymer / titanium dioxide photoanode synthesized by any one of the methods described in claims 1-6.

8. An application of the ultrathin perylene imide polymer / titanium dioxide photoanode as described in claim 7, characterized in that: It is used as a working electrode in photoelectrochemical water splitting for hydrogen production.

Citation Information

Patent Citations

  • Preparation method and application of perylene diimide-urea polymer

    CN108579806A

  • Preparation method and application of ultrathin two-dimensional phosphoric acid regulated metal phthalocyanine / perylene bisimide composite photocatalyst

    CN112791747A

  • Photoanode material for hydrogen production through water decomposition and preparation method and application of photoanode material

    CN115466981A